Effectiveness Of Tgt And Stad Models In Enhancing Motivation And Accounting Learning Outcomes: Efektivitas Model Tgt Dan Stad Dalam Meningkatkan Motivasi Dan Hasil Belajar Akuntansi - Lestari, Wahyu; Isnawati, Dian (Universitas Negeri Yogyakarta, 2025)
This study examines the differences in effectiveness between the Teams Games Tournament (TGT) and Student Teams Achievement Divisions (STAD) learning models in enhancing students' learning motivation and accounting learning outcomes. A quasi-experimental approach with a pretest-post-test control group design was employed, involving experimental and control classes. The population in this study consisted of 250 tenth-grade accounting students from SMKN 1 Bantul and SMK YPKK 2 Sleman. The sample used was 126 students, comprising two classes from each school. A random sampling technique was used to determine the experimental and control classes. Data analysis included descriptive statistical tests, N-Gain score tests, and independent sample t-tests. The findings reveal significant differences in effectiveness between the TGT and STAD models. In terms of learning motivation, the N-Gain score for the TGT model at SMKN 1 Bantul (0.576) was higher than that of the STAD model (0.482), and a similar pattern was observed at SMK YPKK 2 Sleman (0.580 > 0.471). Regarding learning outcomes, the TGT model also outperformed the STAD model, with an N-Gain score of 0.766 compared to 0.621 at SMKN 1 Bantul, and 0.713 compared to 0.599 at SMK YPKK 2 Sleman. These results indicate that the TGT model is more effective in increasing both students’ motivation and accounting learning outcomes compared to the STAD model. The study suggests that teachers should consider implementing the TGT model in accounting instruction, as it fosters higher engagement and better academic performance.